Drive it right - Allstate Insurance Company; Discovery Education (Firm) ([S.l.] : Discovery Communications, Inc., 2007)
"Addresses the root causes of teen driving crashes: teen attitudes, misconceptions, and mindset. Featuring candid testimonials from teens whose lives were drastically changed by auto accidents, the program urges teens to understand, talk about, and create solutions for the root issues that surround most teen motor crashes and deaths."--Container.
"GR 9-12"--Container.
DVD.
Keywords: Automobile driver education